Pembatalan Sertifikat Hak Atas Tanah Akibat Kelalaian BPN dan sebagai Pelaksana Putusan Pengadilan - MHD. Arfan Marjawi Lubis (Jurnal Smart Hukum (JSH), 2022)
This study aims to determine the factors that resulted in the cancellation of land title certificates, the juridical consequences of procedural errors in certificate research by the Medan Administrative Court, and the judge's consideration/decision on the cancellation of land rights certificates. This study uses a descriptive method through a normative approach (legal research) to obtain secondary data and an empirical approach (juridical sociological), to obtain primary data through field research (field research). The factors that resulted in the cancellation of the certificate of title to land were due to defects in administrative law and court decisions. Cancellation of the certificate of ownership of land can result in nullification, null and void and can be canceled. The results of the study indicate that the legal certainty of land rights certificates on the implementation of court decisions that have permanent legal force by permanent decisions cannot provide legal certainty to rights holders. Because with the negative publication system, there is still an opportunity to file a lawsuit/dispute on state administration by other parties. In this case, the court's decision to cancel the certificate does not automatically become invalid, because the cancellation must still be carried out by the National Land Agency. For this reason, it is necessary to have rules in the administration of land that can be a legal umbrella in providing certainty of rights to objects of land rights that have been disputed in the judiciary and have permanent legal force and the need to apply sanctions for land officers who are negligent in carrying out procedures.